Fundamentals of environmental and toxicological chemistry : sustainable science - Manahan, Stanley E. (2013)
"Environmental Toxicological Chemistry for Sustainable Chemical Science covers environmental chemistry, including toxicological chemistry, at the university level. Readers with a basic knowledge of general chemistry and organic chemistry can readily understand the material in the text. Furthermore, for readers who may not have this background, basic chapters are included at the end of the text which will enable them to acquire the fundamentals of general and organic chemistry required to master the material in the text"--
Keywords: Environmental chemistry; SCIENCE / Chemistry / General; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Environmental Science